Microsoft office excel 2007 for project managers - Heldman, Kim (Wiley Pub, 2007)
Combine the power of Excel 2007, Microsoft Office SharePoint Server, and sound project management tools to boost your skill set and maximize your productivity. You’ll walk through a project and learn how to use these powerful tools to schedule jobs, create budgets, manage processes, and share project information. Whether new to project management or a veteran, you’ll discover techniques, hints, and examples you can use immediately.